2009
DOI: 10.3899/jrheum.081164
|View full text |Cite
|
Sign up to set email alerts
|

Health-related Quality of Life and Its Relationship to Patient Disease Course in Childhood-onset Systemic Lupus Erythematosus

Abstract: HRQOL with cSLE is significantly lower than that reported in healthy populations. Organ-specific involvement with cSLE has a differential effect on HRQOL. Higher disease activity and damage are associated with significantly lower HRQOL as measured by the PedsQL-RM and the CHQ-PHS, and worsening of cSLE leads to a further decline.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
80
1
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 69 publications
(89 citation statements)
references
References 25 publications
7
80
1
1
Order By: Relevance
“…Our previous research also found jSLE patients to have lower school functioning compared to healthy children (11). Our current study suggests that this decrement is even larger in obese jSLE than non-obese jSLE patients.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…Our previous research also found jSLE patients to have lower school functioning compared to healthy children (11). Our current study suggests that this decrement is even larger in obese jSLE than non-obese jSLE patients.…”
Section: Discussionmentioning
confidence: 63%
“…Our previous research showed that jSLE patients as a group have lower physical functioning domain scores compared to healthy children (11). This study builds on this earlier report and suggests that this is especially true for obese jSLE patients.…”
Section: Discussionmentioning
confidence: 97%
“…When considering the parent or patient perception of jSLE improvement as an external standard, the SRI and PCI both had very low sensitivity despite high specificity. This may be because patients/parents assign different importance to certain disease features compared to the treating physicians, as we have previously reported 29. This finding also suggests that additional patient-reported outcomes are needed to be included in future jSLE clinical trials in order to capture patient and parent-perceived treatment effects adequately 30…”
Section: Discussionmentioning
confidence: 83%
“…The patients may be categorized based on their disease condition, gender, ethnicity, socioeconomic status, and access to or quality of care. Healthrelated quality of life in SLE has been compared with that of controls [26,[58][59][60], groups with other rheumatologic disorders [61], and groups with chronic diseases [58]. Demography-based comparisons have been attempted.…”
Section: Discriminative Patient-reported Outcome Studiesmentioning
confidence: 99%